2018
DOI: 10.1002/ajpa.23433
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐geographic adaptations in the human ribcage throughout a 3D geometric morphometric approach

Abstract: Size results from the lower ribcage are consistent with the hypothesis of larger trunks in cold-adapted populations. The fact that only Greenland Inuit present a differential morphological pattern, linked to a widening of their ribcage, could be caused by differences in latitude. However, other factors such as genetic drift or specific cultural adaptations cannot be excluded and should be tested in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
0
6
0
2
Order By: Relevance
“…The long clavicle of G. b. beringei may also be related to climate, since wide trunks are associated with colder climates among humans (Franciscus & Churchill, 2002; Garcia‐Martinez et al, 2018; Roberts, 1978; Ruff, 1994). Although bi‐iliac (maximum pelvic) breadth was not evaluated in the present study, it was included in another study of 25 gorilla specimens, about half of which overlapped with those in the present study (Boyle, 2019 and Boyle, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long clavicle of G. b. beringei may also be related to climate, since wide trunks are associated with colder climates among humans (Franciscus & Churchill, 2002; Garcia‐Martinez et al, 2018; Roberts, 1978; Ruff, 1994). Although bi‐iliac (maximum pelvic) breadth was not evaluated in the present study, it was included in another study of 25 gorilla specimens, about half of which overlapped with those in the present study (Boyle, 2019 and Boyle, pers.…”
Section: Discussionmentioning
confidence: 99%
“…The long clavicle of G. b. beringei may also be related to climate, since wide trunks are associated with colder climates among humans (Franciscus & Churchill, 2002;Garcia-Martinez et al, 2018;Roberts, 1978;Ruff, 1994). Although bi-iliac (maximum pelvic)…”
Section: Climatementioning
confidence: 99%
“…Previous researches have shown that Eskimo/Inuit axial skeletons have several characteristics that may be linked to morphological traits, adaptive to the Arctic environmental conditions. These are persistent tendencies towards caudal shift in spine patterning in Asian and North American samples (Karapetian & Makarov, 2019; Merbs, 1974; Stewart, 1932); ribs showing less curvature and torsions in Greenland Inuit (García‐Martínez et al, 2018) and large, barrel‐shaped rib cage in Asian Eskimo (Klevtsova & Smirnova, 1974). It is plausible that there are other characteristics not explored previously.…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns have since been intensely studied and debated (Geist, 1987; Meiri & Dayan, 2003; Symonds & Tattersall, 2010) across a wide range of taxa that includes birds (Fan et al, 2019; Yom‐Tov et al, 2006) and a variety of mammals (Alhajeri & Steppan, 2016; Gohli & Voje, 2016; Yom‐Tob & Nix, 2008). Modern human body proportions have been found to align with Bergmann's and Allen's rules, with populations in colder climates associated with wider bi‐iliac breadths, larger cranial and ribcage sizes, smaller statures, and greater body masses relative to those closer to the equator (Foster & Collard, 2013; García‐Martínez et al, 2018; Ruff, 1994). Conversely, Neanderthal remains effectively highlight many characteristics that are believed to be cold‐adapted in the postcrania, including relatively short limbs and distal limb segments (crural/brachial indexes), as well as large diaphyses and articular surfaces (Buck et al, 2018; Holliday, 1997; Pearson, 2000).…”
Section: Introductionmentioning
confidence: 99%